Perspectivas teológicas para o combate à idolatria - Ribeiro, Claudio de Oliveira ca. 20./21. Jh. (Revista eclesiástica brasileira, 2005)
Having as background Paul Tillich’s theological approach, the Author points to some perspectives that could enrich the present Latin American theological-pastoral panorama and consequently reduce the risk of idolatries. Among these perspectives, he focuses in particular on the emphasis given to the balance between the inter-historical and transcendental dimensions of the category Kingdom of God (challenging some sectors of the Theology of Liberation as well as of the Theology of Prosperity); on the inter-religious dialogue from which is demanded a reflection about the place of the salvific dimension; and on the valorization of the biblical-sapiential tradition vis a vis the Exodus’ tradition, all useful instruments in the struggle against the Latin American social-religious degradation.